Clinical pharmacy and therapeutics - Nanjwade, Basavaraj K.; Patel, Jigar M. (New Delhi : CBS Publishers & Distributors, 2011)
A practical guide for the treatment of common diseases, this updated edition includes the very latest information. It covers the treatment of disease by drug therapy and uses case studies to illustrate the application of the principles discussed
Preface -- Chapter 1 Introduction to Clinical Pharmacy -- Introduction -- Aim of Clinical Pharmacy -- Basic components of Clinical Pharmacy-- Objectives of Clinical Pharmacy -- Scope of Clinical Pharmacy -- Role of Clinical Pharmacy services -- Review Questions -- Chapter 2 Basic concepts of Pharmacotherapy -- Introduction -- Clinical Pharmacokinetics -- Individualization of Drug therapy -- Special precautions in drug usage during infancy and in the elderly (pediatrics and Geriatrics).. 2.5 Drug usage in pregnancy and lactation-- Drug reactions.. 2.7 Drug interactions. 2.8 Interpretation of clinical Laboratory tests.. ............ Review Questions.. Chapter 3 Disorders of Organ systems and their Management Part A Cardiovascular diseases 3.1 Hypertension. 3.2 Congestive heart failure. 3.3 Angina.3.4 Acute myocardial Infarction... 3.5 Cardiac Arrhythmias.. Part B CNS Disorders 3.6 Epilepsy.. 3.7 Parkinsonism. 3.8 Schizophrenia depression. Review Questions. Chapter 4 Respiratory Diseases and Gastrointestinal D Part A Respiratory Disorders 4.1 Asthama -- Part B Gastrolntestinal Disorders 4.2 Peptic ulce . 4.3 Ulcerative Colitis. 4.4 Hepatitis. 4.5 Cirrhosis ..... Review questions. Chapter 5 Part A Endocrine Disorders S.1 Diabetes Mellitus... 5.2 Thyroid Disorders.. Part B Infectious Diseases 5.3 Tuberculosis.. 5.4 Urinary tract infection.. 5.5 Enteric infections.. Review questions. Chapter 6 Part A Hematopoietic Disorders 6.1 Anemia.. Part B Joint and connective tissue disorders 6.2 Rheumatic Disorders. 6.3 Hyperuricemia. 6.4 Gout. -- Part C Nooplastic divene 6.5 Acute Leukomias.. 6.6 HodgKin's disonse.. Review questions.. Chapter 7 Therapeutle Drog Monitoring(TDM) 7.1 Introduction.. 7.2 Criteria for Therapeutic Drug Monitoring. 7.3 Considerations for TDM. 7.4 TDM: Therapeutic and Toxic range.. Review questions ....... Chapter 8 Concept of Essential and Rational drug use 8.1 Introduction.. 8.2 The problem of irrational use of drugs.. 8.3 Assessing the problem of Irational use. 8.4 Quantitative Methods. 8.5 Qualitative Methods.. 8.6 Selected WHO/INRUD drug use indicators(WHO, 1993). 8.7 Overview of intervention strategies.. 8.8 WHO/INRUD 12 core interventions to promote more rational use of drugs Review questions.. References and Bibliography.
Includes bibliographical references.
Keywords: Chemotherapy; Pharmacology; Therapeutics; Pharmacy; Drug Therapy; Pharmacology, Clinical